2002
DOI: 10.12968/bjcn.2002.7.9.10657
|View full text |Cite
|
Sign up to set email alerts
|

Minor illness in children: parents’ views and use of health services

Abstract: Consultation rates in young children are high, and parents and carers of young children have reported feeling disempowered and anxious when their children display common symptoms. Parents have stated that more information would help them manage these symptoms appropriately. This focus group study explored how parents and carers of young children feel when their child displays common symptoms, what information they need to assist them in appropriate management, and to determine if they would value an educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…McIntyre et al. (2003) and others (Kai 1996a, Allen et al. 2002) have also cited parental worry about bothering a doctor for minor illness as a factor involved in decision‐making related to undertaking a health behaviour, medicine use or professional consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McIntyre et al. (2003) and others (Kai 1996a, Allen et al. 2002) have also cited parental worry about bothering a doctor for minor illness as a factor involved in decision‐making related to undertaking a health behaviour, medicine use or professional consultation.…”
Section: Discussionmentioning
confidence: 99%
“…2008). Other studies have reported that parents sought advice from family and friends or a pharmacist prior to consulting a doctor (Neill 2000, Allen et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Two qualitative focus group studies reported that parents sought help from families and friends following negative experiences of seeking advice from health professionals [14], and found that younger mothers sought information on-line to support their own beliefs and to counter conflicting advice offered by health professionals [15]. Sociological reports suggest that the public may become more sceptical of medical authority due to increased access to medical knowledge via the internet [16].…”
Section: Introductionmentioning
confidence: 99%
“…A UK study of mothers' use of pharmacists for childhood health concerns reflected the importance of branded medicines, and the use of the pharmacist as an alternative or stepping stone to the doctor [11]. A UK study found that families and friends were consulted by parents after a negative experience with health professionals [12]. Many studies of information sources report the perception of parents about their preferred sources: it is important to know how these reported preferences might compare with actual behaviour, through the reported sources that influence a specific medicine purchase.…”
Section: Introductionmentioning
confidence: 99%